2020
DOI: 10.1038/s41594-020-0472-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for STAT2 suppression by flavivirus NS5

Abstract: Suppressing cellular signal transducers of transcription 2 (STAT2) is a common strategy viruses use to establish infections, yet the detailed mechanism remains elusive due to lack of structural information of the viral-cellular complex involved. Here, we report the cryo-EM and crystal structures of human STAT2 (hSTAT2) in complex with the non-structural protein 5 (NS5) of Zika virus (ZIKV) and dengue virus (DENV), revealing two-pronged interactions between NS5 and hSTAT2. First, the NS5 methyltransferase and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 63 publications
(65 reference statements)
3
67
0
Order By: Relevance
“…Finally, similar to ZIKV, DENV NS5 mediates human STAT2 degradation in a proteasome dependent manner [ 114 ]. This similarity is highlighted by a recent study that found the specific interacting residues of NS5 and its binding mode with human STAT2 were highly conserved between ZIKV and DENV [ 115 ]. However, in contrast to ZIKV this requires natural viral processing of NS5 from the polyprotein and is dependent on the ubiquitin ligase UBR4 [ 116 ].…”
Section: Common Strategies Employed By Flaviviruses To Evade the Imentioning
confidence: 83%
“…Finally, similar to ZIKV, DENV NS5 mediates human STAT2 degradation in a proteasome dependent manner [ 114 ]. This similarity is highlighted by a recent study that found the specific interacting residues of NS5 and its binding mode with human STAT2 were highly conserved between ZIKV and DENV [ 115 ]. However, in contrast to ZIKV this requires natural viral processing of NS5 from the polyprotein and is dependent on the ubiquitin ligase UBR4 [ 116 ].…”
Section: Common Strategies Employed By Flaviviruses To Evade the Imentioning
confidence: 83%
“…Thus, the interaction of NS5 with cyclophilins and the corresponding inhibition by cyclosporins [ 43 ], Hsp70 [ 44 ], and with a great number of proteins related to the regulation of the immune system has been described [ 45 ]. In fact, most flavivirus NS5 interactions described so far are with proteins related to the interferon response [ 46 ], such as Hsp90 and JAK/STAT, among others [ 47 , 48 , 49 , 50 ]. It seems that the nuclear location of NS5 is not relevant to this type of modulation of the immune response [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…STAT1 and 2 are central to IFN signalling and thus are common targets for viral antagonism (Harrison and Moseley, 2020), however structural details of STAT:antagonist complexes have remained elusive with a few exceptions. The complex of SeV C protein with the N-terminal domain of STAT1 indicates that C protein interferes with the oligomeric state of STAT1 (Oda et al, 2015) whilst the structures of dengue and Zika virus NS5 proteins in complex with STAT2 revealed that both NS5 proteins overlap the IRF9 binding site to prevent ISGF3 assembly (Wang et al, 2020). A similar mechanism was described for measles V protein (Nagano et al, 2020).…”
Section: Discussionmentioning
confidence: 65%